2002
DOI: 10.1080/15428110208984727
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Variability in Biomonitoring Data Using a Large Database of Biological Measures of Exposure

Abstract: Although intra- and interindividual sources of variation in airborne exposures have been extensively studied, similar investigations examining variability in biological measures of exposure have been limited. Following a review of the world's published literature, biological monitoring data were abstracted from 53 studies that examined workers' exposures to metals, solvents, polycyclic aromatic hydrocarbons, and pesticides. Approximately 40% of the studies also reported personal sampling results, which were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 0 publications
1
11
1
Order By: Relevance
“…Thus, differences in metabolite excretion should be noted during metabolic studies using urine as the biofluid. Urine metabolite variability has been seen in earlier metabolomic studies; such as public health and exposure limits to certain agents (Symanski and Greeson 2002). The metabolite variability observed in our human study is similar to that found in studies by Tate (Tate et al 2001) and Holmes (Holmes et al 2000).…”
Section: Sampling Timesupporting
confidence: 86%
“…Thus, differences in metabolite excretion should be noted during metabolic studies using urine as the biofluid. Urine metabolite variability has been seen in earlier metabolomic studies; such as public health and exposure limits to certain agents (Symanski and Greeson 2002). The metabolite variability observed in our human study is similar to that found in studies by Tate (Tate et al 2001) and Holmes (Holmes et al 2000).…”
Section: Sampling Timesupporting
confidence: 86%
“…This becomes critical when evaluating the magnitude of exposure measurement error since improperly specifying the mean structure can result in biased estimates of the variance components [Symanski et al, 1996]. In addition, if measurements closer together in time are more highly correlated than those spaced farther apart, then variance components and functions thereof estimated from models that ignore serial correlation may be biased as shown previously [Symanski and Greeson, 2002] and in this investigation. While we found little evidence of serially dependent measurements (<15% of the data), the residence time of a biomarker should be factored into decisions regarding the longitudinal design of a study and the analytic approaches used for modeling the correlation structure among multiple measurements collected on the same individual.…”
Section: Discussionmentioning
confidence: 80%
“…The database contributing measurements analyzed in this study has been described elsewhere [Symanski and Greeson, 2002]. Briefly, biological monitoring data were abstracted from 53 studies reported in the peer-reviewed literature that examined workers' exposures in myriad industries worldwide.…”
Section: The Databasementioning
confidence: 99%
“…Many studies have found correlations of key metabolites with particular diseases, metabolites that may be used for diagnosis, or changes that may arise due to laboratory conditions of the study (Brindle et al, 2002;Coen et al, 2005;Sabatine et al, 2005). Human urine studies have found changes in metabolite concentrations as a result of age and diet, variation in urine metabolite concentrations within large populations, and variation of particular urine metabolites in individuals over time (Guneral and Bachmann, 1994;Dyer et al, 1997;Zuppi et al, 1997;Symanski and Greeson, 2002;Lenz et al, 2003Lenz et al, , 2004Bollard et al, 2005). Studies of animal urine have found metabolic differences within genetically similar animal models (Holmes et al, 2000;Tate et al, 2001).…”
Section: Introductionmentioning
confidence: 97%